Intrakranielle Gefäßmalformationen = Intracranial vascular malformations - Vollherbst, Dominik; Bendszus, Martin; Möhlenbruch, Markus Alfred (Der Nervenarzt, 2018)
Intracranial vascular malformations range from incidental asymptomatic vascular alterations up to life-threatening vascular disorders. Arteriovenous malformations and dural arteriovenous fistulas are cerebral vascular malformations with arteriovenous shunting of blood. In the majority of cases they are accompanied by an elevated risk of intracerebral hemorrhage and can cause severe symptoms. They can be treated conservatively or interventionally via microneurosurgery, endovascular embolization and radiation therapy. Cavernous malformations, developmental venous anomalies (DVA) and capillary telangiectasia are cerebral vascular malformations without arteriovenous shunting. Cavernous malformations are rarely symptomatic in the form of cerebral hemorrhage, headache or seizures and in such cases an operative treatment can be indicated. The DVA and capillary telangiectasia are usually asymptomatic and do not require treatment.
Gesehen am 28.03.2019